Structural traits dictate abiotic stress amelioration by intertidal oysters. (28th September 2018) - McAfee, Dominic; Bishop, Melanie J.; Yu, Tai‐Nga; Williams, Gray A.
Abstract: Autogenic ecosystem engineers often provide cool microhabitats which are used by associated organisms to reduce thermal extremes. The value of such habitats is, however, dependent on key structural traits of the ecosystem engineer, and the intensity and duration of thermal exposure. Using an experimental mesocosm that mimicked the rocky intertidal environment, we assessed how the spatial configuration of the habitat formed by an autogenic ecosystem engineer, the oyster, influences its capacity to mitigate heat stress experienced by invertebrates during simulated emersion periods on tropical, Hong Kong rocky shores. At the average temperature experienced during summer low tides, oyster habitat ameliorated environmental and organismal temperatures, irrespective of the structural configuration of the oyster bed. As temperatures increased, however, vertically orientated oysters provided microclimates that facilitated cooler invertebrate body temperatures than horizontal beds, which no longer conferred any associational benefit as compared to bare rock surfaces. In the absence of oysters, physiological indicators of stress to associated organisms (i.e., heart rate and osmolality) increased with the intensity and duration of exposure to high temperatures. Such effects were, however, mitigated by association with vertical but not horizontal oyster configurations. In contrast, the osmolality of the oysters was not related to temperature, suggesting they remained in a state of metabolic quiescence throughout emersion. Structural traits such as the spatial configuration of ecosystem engineers are therefore critical to their effectiveness in environmental amelioration. As such, variations in the morphological traits of ecosystem engineers, which have important implications for their ecological role, need to be incorporated into conservation and restoration projects aimed at climate change adaptation. Aplain language summary is available for this article. Abstract : Plain Language Summary